A novel atheroprotective role of MF59-like adjuvant when co-administered with CETP vaccine in rabbit model of atherosclerosis - Aghebati, Tamara (Iran J Basic Med Sci, 2016)
OBJECTIVE(S): In this study, for the first time, MF59 adjuvant was used to develop a cholesteryl ester transfer protein (CETP) vaccine. The efficacy of the vaccine was compared with the efficacy of CETP vaccine formulated with Alum/CpG, the formulation that its immunogenicity has been already demonstrated in rabbit and mice. MATERIALS AND METHODS: Tetanus toxoid- CETP peptide (TT-CETP) was mixed with Alum/CpG or MF59-like and administered subcutaneously for total five times in rabbit model of atherosclerosis. Anti-TT-CETP specific antibody, CETP activity in sera and mRNA level of cytokine IL-4 and IFN-γ in peripheral mononuclear cells were determined. Therapeutic response was also examined by tracking serum lipoprotein levels and pathologic observation of atherosclerotic lesions at aortic site. RESULTS: More anti-TT-CETP antibody was found in Alum/CpG vaccinated rabbits compared to buffer (P<0.001). Antibody induced by MF59-like formulation was not significantly higher than buffer. CETP activity and lipoprotein levels were not significantly different between vaccinated and control rabbits. The mRNA level of IL-4 was significantly lower than buffer while, IFN-γ gene expression was significantly higher in both vaccinated groups. Atherosclerosis thickness grade of aorta was dramatically lower than buffer (P<0.01) in both vaccinated groups. CONCLUSION: It is concluded that MF59-adjuvanted CETP vaccine showed anti-atherosclerosis properties, but the protective effect could not be directly attributed to the immune response induced by anti TT-CETP antibody and CETP inhibition. Further studies are needed to explain the anti-atherosclerosis properties of MF59 in the presence of TT-CETP peptide.